Out of Class Peer Group Discussion in Learning Basic English Grammar and Its Impact on the Students’ Grammatical Knowledge - Wisma Yunita (Universitas Negeri Padang, 2014)
The broad scope of knowledge on English grammar while the number of course credits offered in the curriculum of an English study program at university is limited made the grammar teachers seek for ways to keep on transferring the knowledge to the students to their best. One of the ways to reach the aim is by using out of class peer group discussion in the teaching and learning of English grammar. This research is a descriptive research aiming at finding out the impact of using out of class peer discussion in learning Basic English grammar. The subject of the research was 38 freshmen students of the English Education study program of University of Bengkulu enrolled in 2013-2014 academic year who took a course named Structure I. The data was taken by using eight open questions given to the students and by using students’ individual and group study journal which was analyzed by using Gay and Airasian (2000). The research result shows that the students have better English grammar knowledge, become more confident in speaking English, become closer to their friends, feel happier and more comfortable to learn in group with their own classmates, can share ideas and knowledge with others and are more confident in using English language.